PERAN BUZZER MEDIA SOSIAL DALAM MEMPERKUAT EKOSISTEM PEMASARAN DIGITAL - Bambang -- Arianto (Optimum: Jurnal Ekonomi dan Pembangunan, 2020)
This article explains the role of social media buzzers that discuss the Pasar Kakilangit Mangunan Bantul to residents through hashtags which have become trending on Twitter topics. With creative content such as; videos, memes and texts, social media buzzers receive unique approval from Kakilangit Market to citizens. Through the hashtag #PasarKakilangit which can be included in the Twitter Indonesia trending topic, the buzzers together support the promotion of Pasar Kakilangit products to viral and widely known by citizens. The presence of social media buzzers has built a new culture and new knowledge of the importance of trending Twitter topics in increasing the promotion of digital products and services. This article proves that media buzzer has supported positively in strengthening the digital marketing ecosystem.